The Demographic Variables as the Predictors of the Teaching Competencies of Online Instructors in the Universities of Pakistan - BIBI, MARIA; KHURSHID, Dr. FARHANA (The journal of contemporary issues in business and government, 2021)
In Pakistan, higher education institutions are focus to increase the integration of information and communication technologies into teaching the curriculum and programs. The demographic variables of the instructors influence the teaching competencies of the instructors. The main aim of this research is to identify the influences of the demographic variables on the teaching competencies of the instructors in a virtual setting. The improvement and utilization of technological tools influence to improve online education. The ‘online teaching competencies (OTCs) matrix was applied as the theoretical framework for the current research. An exploratory study was conducted in the three universities of Pakistan those who are offering online programs and courses to their students. The sample of the study was consist of 250 online instructors. Data was collected through a standardized Five-point Likert scale questionnaire developed by (Bigatel, Ragan, Kennan, May, &; Redmond, 2012). Multiple regression analysis was applied to analyze the data. The finding shows that the demographic variables ‘experience’ and ‘qualification’ influence as compare to the ‘number of professional training events’ and their ‘age’ on the teaching competencies of the instructors. The finding suggested that the quality of the professional training events for the instructors should be conducted and improved.